Management of Hepatic Encephalopathy - G. Wright; A. Chattree; R. Jalan (International Journal of Hepatology)
Hepatic encephalopathy (HE), the neuropsychiatric presentation of liver disease, is associated with high morbidity and mortality. Reduction of plasma ammonia remains the central therapeutic strategy, but there is a need for newer novel therapies. We discuss current evidence supporting the use of interventions for both the general management of chronic HE and that necessary for more acute and advanced disease.